Family Nest - Tarr, Béla; Pap, Ferenc; Horvath, Laszlone; Horváth, László; Kun, Gábor (Facets Video, 2005)
In his award-winning debut feature, Béla Tarr brings the dramas of everyday life to the big screen in a style that is a compelling as it is real. Celebrated for his nihilistic tales of desperate people unable to escape their human or social conditions, Tarr is one of the most distinctive talents in world cinema. A young couple is forced to live with the husband's parents in a one-room apartment because of a housing shortage in communist Hungary. The proximity of too many people in a small space results in endless arguments, which take their toll on the couple's marriage and family. Shot in a documentary style, "Family Nest" captures the lives of an ordinary family in a broken society. This impressive debut by Tarr shared the Grand Prize at the Mannheim International Filmfest and was named Best First Feature by the Hungarian Film Critics. [Cover]